Implementasi Moderasi Beragama sebagai Langkah Preventif Terbentuknya Radikalisme di Kalangan Siswa - Tiyas, Mutiah Cahyaning; Khadavi, M Jadid (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This research aims to examine the implementation of religious moderation as a preventive measure for the formation of radicalism among students. The students' heterogeneous religious backgrounds and school programs that are oriented towards high tolerance practices make researchers interested in studying the implementation of religious moderation-based learning programs at SMA Negeri 4 Probolinggo City. This research is Field Research, namely qualitative research with analytical descriptive characteristics. The presentation of data in this research is formatted in narrative form with data collection using observation, interview, documentation and analysis of natural documents for each discussion. The research informants consisted of the Principal, Deputy Head of Curriculum, Deputy Head of Student Affairs, Teachers and Students. The research results show that SMAN 4 Probolinggo has implemented the practice of tolerance values ​​which are manifested in the learning process and extracurricular activities. The School Bullying Agent Program (APS) is an important alternative in preventing and resolving problems regarding bullying and religious violence. SMA Negeri 4 Probolinggo City plays an active role in the activities of the Religious Harmony Forum (FKUB) which is designed to strengthen tolerance and harmony between religious communities in the school environment. The school curriculum is designed to achieve the target of graduates who have a more inclusive and open understanding in preventing the formation of radicalism and strengthening moderate attitudes among students.